Remarks on numerical simulation of the LEAP-Asia-2019 centrifuge tests. Issue 142 (March 2021) - Chen, Long; Ghofrani, Alborz; Arduino, Pedro
Abstract: Prototype and physical scale numerical models were created using OpenSees to simulate centrifuge experiments representing a sloping ground condition in accordance with LEAP-Asia-2019 guidelines. The PM4Sand constitutive model calibrated for Ottawa F65 sand was used. Simulated results showed reasonable agreement between prototype and physical centrifuge test scale models. Modeling fundamental characteristics of the centrifuge experiment, e.g., direction of shaking relative to the axis of centrifuge, was found to be an important factor in achieving a better match between numerical and experimental results for the simulation of the prototype model. A preliminary study on the use of generalized scaling laws showed that models with higher initial stresses predict larger lateral displacements. Additionally, examination of stress histories recorded in simulations and experiments indicated higher cyclic stress ratios and static shear stresses are required for proper calibration of constitutive model parameters. Highlights: Prototype scale and physical scale numerical models are created. PM4Sand constitutive model is calibrated for Ottawa F65 sand. Prototype scale model predicts greater lateral displacement in tangential shaking cases due to effect of boundary conditions. Under similar input motions and relative densities, model with higher initial stresses predicts larger lateral displacements. High cyclic stress ratio and static shear stress need to be focused during model calibration process.